Application of response surface methodology for bioactive compounds extraction and the variability in phytochemical profile from roots of Ammi visnaga (L.) Lam. - El Jabboury Zineb; Aazza Smail; Benjelloun Meryem; El Ghadraoui Lahsen (BIO Web of Conferences, 2024)
Ammi visnaga L. Lam. is the most popular therapeutic plant in the Mediterranean region. Umbel is a traditional Moroccan remedy for diabetes, and oral care. The main goal of this study was to determine which extractor solvents had a particular affinity for the total phenolic content (TPC) found in the roots of Ammi visnaga. Using solvents chosen from the first step, the phenolic contents were maximized using the mixture design response surface methodology. The optimal solvent mixes of 10% methanol, 50% water, and 40% ethanol were used to prepare the root extracts. This study was designed to examine the phenolic profile of Moroccan Ammi visnaga L. roots using UHPLC/DAD–MS/MS Assessing the antioxidant capacities with the use of four complimentary tests (TAC, TPC, CUPRAC, and HCA). The obtained results showed the peak of antioxidant activity TAC (10.17±1.4 mg/g AAE) and TPC (15,99±0,4 mg GAE/g)).Various bioactive compounds (21 components) with different concentrations were identified, including isorhamnetin 3-O-glucoside (25.8%),and isorhamnetin 3-O-rutinoside (22.3%), which are the three most abundant individual phenolic compounds. The findings revealed the presence of numerous bioactive substances with important biological capabilities in the roots of A. visnaga L., emphasizing the need for further experimental model validation of the data.